The Effect of Competency and Training on Employee Performance in The Procurement Division of PT Bio Farma (Persero) With Job Satisfaction as a Mediation Variable - Rafli Mahdavika Ramadhan; Fariz Fariz (The Eastasouth Management and Business, 2026)
Employee performance is one of the most important factors in maintaining organizational effectiveness and operational sustainability, particularly in the pharmaceutical industry which requires high standards of accuracy, efficiency, and compliance. This study aims to analyze the effect of competence and training on employee performance with job satisfaction as a mediating variable at the Procurement Division of PT Bio Farma (Persero). This study employed a quantitative explanatory approach using SEM-PLS. Data were collected through questionnaires distributed to 60 employees of the Procurement Division of PT Bio Farma (Persero). The independent variables in this study are competence and training, the dependent variable is employee performance, and the mediating variable is job satisfaction. The results indicate that competence has a positive and significant effect on job satisfaction, and training also has a positive and significant effect on job satisfaction. However, competence and training do not have a significant direct effect on employee performance. Furthermore, job satisfaction was unable to mediate the relationship among competence and training on employee performance. These findings imply that competence and training primarily contribute to improving employees’ work comfort, confidence, and understanding rather than directly enhancing performance outcomes. Therefore, companies should also consider other factors influencing employee performance, such as organizational culture, work environment, leadership, and motivation systems.